1992
DOI: 10.1007/bf00220476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a 17q11.2 translocation in a malignant schwannoma cell line

Abstract: Malignant schwannomas are soft-tissue neoplasms that occur at increased frequency with germline alterations of the neurofibromatosis-1 (NF1) gene at 17q11.2. We report molecular and cytogenetic characterization of a malignant schwannoma cell line established from an individual affected with NF1. This cell line has a complex hyperdiploid karyotype with two cytogenetically identical der(13)t(13;17)(p11,q11.2) chromosomes. Using somatic cell hybrids, we mapped twelve chromosome-17 probes to either the der(13)t(13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
0
24
1
2
Order By: Relevance
“…These allelotyping results show that the cell lines originate from monoclonal tumors, but despite their monoclonality, there seems to be a residual DNA contribution from a non tumorous tissue, as evident from the minimal signal of the ''lost allele.'' In this regard, it is worth noting that a 17q11.2 translocation has been characterized previously in a MPNST cell line (33) and that recombination hotspot in NF1 microdeletion patients has been characterized as well (35).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These allelotyping results show that the cell lines originate from monoclonal tumors, but despite their monoclonality, there seems to be a residual DNA contribution from a non tumorous tissue, as evident from the minimal signal of the ''lost allele.'' In this regard, it is worth noting that a 17q11.2 translocation has been characterized previously in a MPNST cell line (33) and that recombination hotspot in NF1 microdeletion patients has been characterized as well (35).…”
Section: Resultsmentioning
confidence: 88%
“…We assume that the ST88-14 cell line contains a pathogenic inactivating mutation, as yet undetected. In fact, this cell line was shown previously to contain a karyotypically complex gene rearrangement involving 17q and to display allelic loss of 17q (33).…”
Section: Resultsmentioning
confidence: 94%
“…No mutations were detected in the coding region of the NF1 gene in either sporadic MPNST sample (data not shown). Loss of heterozygosity (LOH) at the NF1 locus has previously been confirmed in five of the six NF1-associated MPNST lines (8,25,26).…”
Section: Resultsmentioning
confidence: 88%
“…Over a 5 day period, GIST882 proliferation was consistently inhibited by STI571 concentrations 50.1 mM (Figure 2). In contrast, cell proliferation was not inhibited by even 10 mM STI571 in any of the four comparison sarcoma cell lines, including the malignant peripheral nerve sheath tumor cell line ST88-014 (Figure 2, Reynolds et al, 1992), the ®brosarcoma cell line HT-1080 (not shown, Rasheed et al, 1974), and immortal cell lines established from malignant peripheral nerve sheath tumors and mesotheliomas (data not shown). Although ST88-014 has been reported to express c-KIT and respond to exogeneous SCF (Badache et al, 1998), we did not supplement the cultures with SCF and therefore could not determine whether STI571 inhibits the KIT/SCF pathway in MPNST 88-014.…”
Section: Abstract: Gastrointestional Stromal Tumors (Gist); C-kit; Stmentioning
confidence: 90%